Nonrecurrent laryngeal nerve-an anatomical deviation - Sivakumar, E.; Swapna, C. A.; Karanam, Lavanya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Thyroidectomy is one of the most dispute and discussed surgery. Identification of recurrent laryngeal nerve is the most important step in this surgery. Among postop complications of thyroidectomy, the commoner is haematoma, transient hypocalcaemia and hoarseness. We report a rare case of nonrecurrent laryngeal nerve in a 25-year-old male with swelling in the right thyroid lobe. A 25-year-old male presented to the ENT OPD with complaints of swelling in thyroid region for 6 months with no other symptoms. On examination there was a 2×3 cm size nodule in the right lobe of thyroid. Rest of ORL examination was normal. On ultrasonogram there was an enlarged right lobe of thyroid with a nodular goitre. Fine needle aspiration cytology showed colloid goitre. Patient was planned for right hemithyroidectomy. Right side type 1 nonrecurrent laryngeal nerve was identified at the level of superior pole of thyroid branching from vagus and entering the larynx at the level of cricothyroid joint was identified intraoperatively. In conclusion, nonrecurrent laryngeal nerve though a very rare anomaly forms a crucial anatomical structure in thyroid surgery and is prone to injury. It is one of the preventable complications during thyroid surgery leading to postop vocal cord palsy. An in-depth anatomical knowledge and diligent surgical technique will help in identification and preservation of nonrecurrent laryngeal nerve.